User Experience Evaluation of the SEKAWAN V3 Website Using the User Experience Questionnaire (UEQ) - A'rafi Laksmana Dirgantara; Chanifah Indah Ratnasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The SEKAWAN V3 website is used as a thesis management system in the Informatics Study Program at Universitas Islam Indonesia. However, preliminary observations indicate usability issues affecting user interaction. This study aims to assess the user experience of SEKAWAN V3 and analyze the impact of a UI/UX redesign based on user feedback. The study applies the User Experience Questionnaire (UEQ) supported by open-ended responses. A total of 23 participants were involved, with 17 valid responses in the initial evaluation and 22 valid responses in the re-evaluation after data consistency filtering. The initial results reveal issues related to navigation clarity, feature understanding, and interface structure. Based on these findings, a redesigned prototype was developed and evaluated. The results indicate improvements across all UEQ dimensions, particularly in stimulation, attractiveness, and perspicuity, suggesting better engagement, visual appeal, and ease of use. Qualitative findings support these results, showing that users perceive the system as clearer, more structured, and more intuitive. This study demonstrates that combining quantitative and qualitative approaches can support data-driven improvements in system design.